Strategic Marketing Formulation Through External And Internal Analysis : A Case Study of Mekar Bersorai Florist - Nabilah Khairunnisa, Zulfa; Perdhana Dalimunthe, Gallang (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Since the end of 2024, Mekar Bersorai faces a critical business challenge due to declining sales performance. The research design adopts a descriptive case study approach focusing on Mekar Bersorai’s core problems of declining sales and customer behavior change. This design enables a deep examination of internal and external circumstances of the flower industry and determination of appropriate marketing solutions to enhance the company’s competitive opportunity. Porter's five forces revealed that the industry has a high level of rivalry and buyer power, as well as high threat of substitute. VRIO analysis showed that even though Mekar Bersorai has a personalization service and unique design ideas, it can still be duplicated by competitors if not structured and organized; the VRIO found a lack of organizational structure, less frequent innovation, and formal processes. This study reveals that the best way of ensuring Mekar Bersorai experiences a recovery is through strengthening its unique brand image, gradual incorporation of technology to enhance service accessibility, and fostering greater customer relationships to create loyalty in a highly competitive market.